Physicochemical properties of starch and prebiotic potential of oligosaccharides from dioscorea hispida - Napisah Hussin
The underutilised Dioscorea hispida Dennst. tuber was processed for its starch and was evaluated for its physicochemical properties. The tuber contained 97.95% total starch comprising of amylose (25.27%) and amylopectin (72.68%). Dioscorea hispida starch contained crude protein (0.42%), crude fat (0.23%), ash (0.4 7%) and crude fiber (0.93%). The starch granules were coarse-surfaced polyhedral shape with an average diameter of 2-4 urn. The starch exhibits B-type in X-ray diffraction pattern and had gelatinisation peak temperature of 87°C and pasting temperature of 78 °C. The swelling power. solubility, water-holding and oil¬holding capacities were 14.22 gig. 5.48 gig, 2.78 gig and 1.14 gig, respectively. Different concentrations of D. hispida starch (5%. 10%, 15%, and 20%) were hydrolysed by individual enzymes a-amylase. amyloglucosidase or pullulanase or combination of the enzymes to yield D. hispida oligosaccharides (DHOS). The maximum yield of DHOS (19.67 mg/g) was obtained from the hydrolysis of 10% (w/v) of D. hispida starch with combination of a-amylase (pH 5.5; 90°C) and pullulanase (pH 5.5; 45°C) for 6 h. The DHOS when analysed for prebiotic characteristics was found to be resistant to hydrolysis by gastric juice at pH 3-4 (88.78-99.76% DHOS residue) for 3 h but less resistant to hydrolysis at pH 1-2. DHOS was also found to be less resistant towards hydrolysis by gastrointestinal tract enzymes and intestinal absorption as the remaining DHOS after hydrolysis was ranging from 40.62-52.04%. In term of bacterial growth study. DHOS positively influenced the growth of beneficial rat faecal rnicroflora (lactobacilli and bifidobacteria) and negatively influenced the growth of detrimental bacteria (bacteroides. clostridia and enterobacteria). The prebioiic index (PI) was calculated to compare the positive effect of DHOS with other prebiotics. The PI of DHOS, fructooligosaccharides (FOS) and inulin after 72 h fermentation were +7.72, +8.69 and +9.27 respectively. Lactic acid and short chain fatty acids (SCFA) were significantly produced in the media containing DHOS. The activity of